POLITICAL REFORM OF LABOR PROTECTION LAW IN THE GLOBALIZATION ERA - Arpangi Arpangi (UNISSULA, 2020)
In its development, economic globalization has created an affiliation between the local economy and the international economy. It resulted in an extraordinary blow to the economic system in third world countries that were trying to become developed countries. It can be seen in the issue of protecting workers' welfare, which is not fair. So, this article intends to discuss related to the protection of workers' welfare in the era of globalization and the weaknesses that affect the protection of labor rights in the era of globalization, which can't realize justice for workers. The article is expected to be able to stimulate each party to re-discuss the issue of protecting labor welfare in the current era of globalization in Indonesia. The results of research produced are The factors that influence injustice in protecting workers' welfare in Indonesia are Legal rule factors, Influence Factors of Globalization can also be concluded that the failure of labor law politics in Indonesia will have an impact on the increasing poverty rate in Indonesia due to increasing unemployment in Indonesia as one of the effects of the flood of foreign workers in Indonesia with the number of employment that is running low.